ASSESSMENT OF AN EFFECT OF SOWING MATERIAL QUALITY AND METHODS OF PRE-SOWING TREATMENT OF SORGHUM SEEDS WITH DRUGS ON PRODUCTIVITY AND DEVELOPMENT OF BACTERIAL STRIPE DISEASE (PSEUDOMONAS ANDROPOGONI) IN THE CONDITIONS OF FORESTRY STEPPE OF THE SAMARA REGION - E. V. Matvienko (Зерновое хозяйство России, 2018)
Pathogen of bacterial stripe disease is the bacteria Pseudomonas andropogoni (E. Smith Stapp), which is widely spread and harmful for sorghum. The first signs of bacterial stripe disease on sorghum leaves usually appear in the first part of July and look as red stripes along the leaf. A rich exudate is formed, which dries as red films or scales under the leaves. The purpose of the study was to assess the effect of sowing material quality and methods of pre-sowing treatment of sorghum seeds with drugs on productivity and development of bacterial stripe disease (Pseudomonas andropogoni) in the conditions of forestry steppe of the Samara Region. Forecasting the emergence of bacterial stripe disease on sorghum leaves and assessing its harm on the field we recommend making accounts of its prevalence and development of the disease in the phase of milk ripeness of grain. The development of bacterial stripe disease of sorghum in the forestry steppe of the Samara Region depends a lot on hydro thermal year conditions, amount of precipitations and air temperature in May, June, July (2011). The important factor of tolerance increase of sorghum to bacterial stripe disease is a sowing of seeds from fully healthy plants. The experiments showed, that the most efficient drugs against bacterial stripe disease of sorghum and for increase of productivity of sorghum were ‘Prestizh’, ‘Grandsil’ and ‘Phytosporin’ for a variety of sweet sorghum ‘Kinelskoe 4’; ‘Prestizh’ and ‘Grandsil’ for varieties of grain sorghum ‘Premiera’ and ‘Ros’. The average coefficients of correlation between the disease and productivity is r = -0,394 – -0,471.